Integration of Ethnochemical Principles in the Preservation of Indonesian Batik Based on Tafsir Al-Maraghi - Irfan Maulana Rohmatulloh; Mochammad Taufiq Ridho (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
This study aims to examine the integration of ethnochemistry principles into the preservation of Indonesian batik through the perspective of Tafsir Al-Maraghi. This research employed a qualitative approach using a literature review by analyzing various scholarly sources related to ethnochemistry, the batik-making process, and the interpretation of relevant Qur'anic verses. The findings indicate that the batik production process, particularly the waxing, dyeing, and wastewater treatment stages, embodies chemical concepts embedded in local community knowledge, representing the practical application of ethnochemistry. Furthermore, the analysis of Tafsir Al-Maraghi reveals that batik symbolizes personal adornment, as reflected in Qur'an Surah Al-A'raf (7):31, while the diversity of colors found in batik corresponds to the meaning of Surah Fatir (35):27, which emphasizes the diversity of Allah's creations as a manifestation of His greatness. Therefore, batik serves not only as a cultural heritage but also as a culturally responsive medium for science education and a means of strengthening Islamic values within society.